Utility of Plasmapheresis in Autoimmune-Mediated Encephalopathy in Children: Potentials and Challenges - Abdulhafeez M. Khair (Neurology Research International)
Autoimmune-mediated encephalopathy in children continues to constitute a diagnostic and therapeutic challenge in pediatric population. Utility and usefulness in this clinical setting of plasmapheresis have seldom been evaluated in current pediatric literature. Children with immune-mediated encephalopathies represent a uniquely different group among patients presenting to intensive care units or neurological services worldwide. Arriving at a final diagnosis is not an easy task for treating physicians. It is very crucial to consider early use of first-line immunotherapy modalities, save those children’s lives and improve outcomes. Plasmapheresis is an emerging, potentially beneficial first-line therapy in such patients. However, indications, value, logistics, and procedural difficulties are often faced. This study is mainly meant to review the current knowledge in regard to the clinical value of plasmapheresis in children with immune-mediated encephalopathy.